Determination of Euler pole parameters for Sundaland plate based on updated GNSS observations in Sumatra, Indonesia - Satrio Muhammad Alif; Kuo-En Ching; Takeshi Sagiya; Widya Nabila Wahyuni (Geoscience Letters, 2024)
Abstract To provide a precise Euler pole parameter of Sundaland plate for earthquake potential evaluation in Sumatra, Indonesia after the 2004 M9.2 Aceh earthquake, we adopted 37 new Global Navigation Satellite System (GNSS) observations in Sumatra and 30 transformed published velocities in Indochina and Malaysia under the International Terrestrial Reference Frame 2014 (ITRF2014). The 37 GNSS data were processed using the software Bernese v.5.2. The GNSS velocities were calculated by the coordinate time series analysis with the least squares method. The grid search algorithm was used in Euler pole parameter estimation, which was validated using the bootstrap resampling. The optimized Euler pole parameters are the latitude of 45.63 ± 0.45°, the longitude of − 88.71 ± 0.38° and the angular velocity of 0.337 ± 0.002°/Myr in counterclockwise direction. Besides, the distinguishable and systematic pattern in space is shown in the residual velocities, which may imply the possibility of minor postseismic deformation, Tibetan crustal flows, or the hypothesis that the Sundaland Plate is composed of several microplates.